Management and arrangement model of Loloan river area for conservation and development as a tourist attraction area - Eryani, I Gusti Agung Putu; Yujana, Cok Agung; Astara, I Wayan Wesna (Fakultas Teknik UB, 2020)
Loloan River is located in the Renon village, which borders the Sanur area that has the potential to become a tourist attraction area. However, the current condition is not yet favorable to be used as a tourist area due to the inadequate management of water potential and the arrangement of the Loloan River area. Therefore, a management model and arrangement of the Loloan river area is needed to optimize the development of the Renon Traditional Village around the Loloan River area as a tourist attraction area. The research method used in this study uses descriptive qualitative research methods to create a management and arrangement model that is appropriate to the research location. Management and arrangement model of Loloan River area aims to optimize the development of the Loloan River area as a tourist attraction area that can be done in several ways, including empowering the society in efforts to clean up sediment in the Loloan River Basin so that the river's capacity can be optimal, educating the society about the importance of conserving irrigation channels for sustainable water potential and arrangements in the Loloan River area which can be done by planting around the Loloan River area.